Donut Production Sigma Level and Strategic Positioning: Tingkat Sigma Produksi Donat dan Posisi Strategis - Rinaldo, Hadid; Sulistiyowati, Wiwik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Quality control and risk management are essential in food-based small enterprises to maintain product consistency and operational stability. Specific Background: UD Darjo’s Donut’s experienced recurring production defects exceeding internal tolerance limits, requiring structured process evaluation and strategic formulation. Knowledge Gap: Limited studies integrate quantitative Six Sigma measurement with strategic SWOT positioning in small-scale donut production systems. Aims: This study aims to measure process capability using the Six Sigma DMAIC framework and formulate business strategies through SWOT analysis. Results: Five dominant defect types were identified, including undercooked dough, burnt surface, inconsistent shape, wrinkled texture, and hollow structure. The average process capability reached 3.78 sigma across six observation periods, with values ranging from 3.64 to 4.00. SWOT mapping positioned the enterprise in Quadrant I, indicating strong internal conditions and favorable market opportunities. Novelty: The study combines sigma-level evaluation with strategic quadrant mapping within a food MSME context. Implications: The findings support structured quality monitoring and aggressive growth strategies aligned with internal strengths and external opportunities. Keywords: Six Sigma, Quality Control, SWOT Analysis, Process Capability, Food MSME Key Findings Highlights Five dominant defect categories were systematically identified in production. Average process performance reached 3.78 across six periods. Strategic mapping indicated a strength-opportunity configuration.